A comprehensive review on vanillin: its microbial synthesis, isolation and recovery. Issue 1 (2nd January 2021) - Paul, Veena; Rai, Dinesh Chandra; T.S, Ramyaa Lakshmi; Srivastava, Suresh Kumar; Tripathi, Abhishek Dutt
ABSTRACT: Vanillin is an extensively used flavor compound valuable in the food and pharmaceutical industries. Vanillin flavoring compound is present as natural, synthetic, and biotechnologically generated. The food safety authorities contemplate biotechnologically-derived vanillin as nature-identical vanillin. This review endeavors to present an overview of the microbial approach for vanillin production. This review summarizes the current trend in the biotechnologically-derived vanillin bioconversion from agricultural byproducts rich in eugenol, ferulic acid, isoeugenol, lignin, and de novo synthesis by bacteria, fungi, and recombinant microbial cells. This review also outlines the enzymes involved in vanillin synthesis. The subsequent section deals with the cultural conditions needed for the enhanced production of vanillin. This review offers broad knowledge about the downstream processes such as isolation, characterization, purification, and recovery. The concluding section describes the limitation in the production process, specifically toxicity and by-product formation, and various strategies to overcome these factors using fermentation technology with adsorbent resins and recombinant microbial cells.